(untitled) (Research, Society and Development, 2024)
Motherhood is marked by an intense search for information, emotional vulnerability and psychosocial and family adjustments. A support network and a sympathetic environment, such as social media, are crucial, where welcoming and health education transcend geographical barriers. The aim was to analyze the sources that address the use of social media for health education during maternity and its individual and social repercussions. The US National Library of Medicine was searched in July 2023, using the descriptors: "social network", "parenting" and "health education", associated with "AND". Included were articles published and indexed in Portuguese and English in the last decade, with the theme explicit in the title or body of the text. Articles with a general theme, prior to maternity, without the use of social networks and not related to health education were excluded. Of the 2,616 articles, 24 met the criteria, from various countries, with the exception of Brazil. The social network facilitates the dissemination of educational information, fosters parental self-confidence and a sense of belonging, reduces stress and the feeling of unpreparedness. It is a means of access for people marginalized from traditional health services. Professionals are wary of health education and of promoting public policies, due to the uncertainty of scientific validity. Third parties have practiced violence and prejudice on the networks. There is a lack of knowledge, inaccessible language and the impossibility of networking between parents of atypical children. Further research covering all social groups is recommended in order to fully assess the consequences of these networks.